As inconvencionalidades do marco legal da biodiversidade frente ao instituto da consulta prévia, livre e informada: um processo de colonialismo biocultural - MIRANDA, João Paulo Rocha de (Universidade Federal do Pará, 2018)
This thesis deals with the incompatibilities of Law No. 13.123/15 with human rights treaties, in the juridical-political context of access to genetic heritage and traditional knowledge associated with biodiversity, called biocultural colonialism. Thus, the main objective of this thesis is to investigate the conventionality or unconventionality of the legal framework of biodiversity. That is, to analyze the compatibility or not of Law No. 13,123/15 with international jushumanist treaties, regarding the right to prior, free and informed consultation of indigenous peoples and traditional communities. For this, this thesis used the deductive and dialogic methods. Deductive, as the research started from the global context of biocultural colonialism to international norms, and from these to the internal norms and the unconventionality of the legal framework of biodiversity, Law 13,123/15. Dialogical, because the analyzes sought to take into account the social, political, economic, environmental, among others. Thus, the discussion about the unconventionality of the legal framework of biodiversity was made in an integrated way to the socioenvironmental, legal and political reality of the country and the world. In addition, a dialogue was held between different sources of international law. In view of this, it was possible to conclude that the legal framework of biodiversity is unconventional, given the various incompatibilities with human rights treaties of a supralegal or materially constitutional nature, depending on the thesis adopted. However, in any case, its unconventionality is confirmed, thus enabling diffuse control of conventionality. This would have the effect of invalidating the domestic norm, less beneficial, and incompatible with human rights treaties.